KANDUNGAN BAHAN KERING DAN KONDISI FISIK LIMBAH PERTANIAN YANG MENDAPAT TEKNOLOGI APLIKATIF Trichoderma sp SEBAGAI PAKAN RUMINANSIA: Dry Matter Content and Physical Condition of Agricultural by-product with Aplicative Technology Trichoderma sp. as Ruminats Feed - Rohmiyatul Islamiyati; ismartoyo ismartoyo; Indrawirawan Indrawirawan (Buletin Nutrisi dan Makanan Ternak, 2022)
Food crops and plantation waste can potentially be a source of ruminant feed. The problem faced is generally low quality. This study aims to analyze the dry matter content and physical condition of several agricultural by-products that received the applicative technology of Trichoderma sp as ruminant feed. The experimental design was completely randomized (CRD) with a 5x3x3 factorial pattern. The first factor is agricultural by-products, including corn straws, sago dregs, banana stalks, rice straws, and cocoa husks. The second factor is the level of Trichoderma sp of 2.5%, 5.0%, and 7.5%. The variance showed that the type of agricultural by-products and the level of Trichoderma sp had a significant effect (P<0.05) on the dry matter content. In contrast, the interaction between the type of by-products and the level of Trichoderma sp had no significant effect (P>0.05) on the dry matter content. It concluded that the higher level of Trichoderma sp increased dry matter, and corn straw had the highest dry matter content.